Can we get there from here? Learning disabilities and future edueation poliey - Spear-Swerling, L. (Perspectives on Learning Disabilities: Biological, Cognitive, Contextual, 2018)
Contemporary educational policies for identifying learning disabilities (LD) have been widely criticized. I would like to begin this chapter with a story that illustrates some of the conundrums in these policies. © 1999 Taylor & Francis.
Journal Abbreviation: Perspectives on Learning Disabilities: Biological, Cognitive, Contextual
Keywords: dept.sed